Scientific Partisanship: The Social Geometry of Intellectual Support. (May 2017) - Michalski, Joseph
Abstract : The article applies D. Black's pure sociology paradigm to examine the degree to which scientific evidence supports ideas deduced from the perspective. The main argument suggests that the empirical support for pure sociology varies inversely with the social distance separating scholars in social space. Moreover, the nature of the evidence adduced and the use of qualitative or quantitative methodologies predictably vary with social distance as well, increasing the likelihood of finding confirming or disconfirming evidence. The study tests these ideas by examining the full range of refereed journal articles ( n = 191) published from 1976 to 2015 with pure sociology as the main focus. L'article utilise le paradigme de la sociologie pure de D. Black afin d'examiner à quel point les évidences scientifiques soutiennent les idées proposées par cette approche. L'argument principal suggère que le soutien empirique pour la sociologie pure varie inversement avec la distance sociale séparant les spécialistes dans l'espace social. De plus, la nature des évidences obtenues et l'utilisation de méthodes qualitatives ou quantitatives varient aussi en fonction de la distance sociale, augmentant la probabilité d'obtenir des évidences confirmant ou réfutant le paradigme. Cette recherche teste ces idées en examinant l'ensemble des articles de revues avec évaluations externes ( n = 191) publiés entre 1976 et 2015 avec la sociologie pure comme focus principal.